Diploma 3 Pharmacy Students’ Perception toward Zoom Application Usage in Learning English during Covid-19 Pandemic - Dewi Sartika; Agus Wahyudi (Edu-Ling: Journal of English Education and Linguistics, 2021)
Most educational institutions use online learning platforms during the Covid-19 pandemic. One of the platforms frequently used is Zoom. This research aimed to describe the diploma 3 pharmacy students’ perceptions of the use of Zoom in learning English. The data were collected through a questionnaire and interviews. 43 diploma 3 of pharmacy students at STIFI Bhakti Pertiwi Palembang participated in this research. Since this research explored diploma 3 of pharmacy students' perception coming from the students' experiences during the Covid-19 pandemic, descriptive research by using qualitative technique was applied. The result of this research was found that diploma 3 pharmacy students got positive perception toward Zoom application usage in learning English because it was accessible and effective. Although the electricity disturbance, internet quota, and the use of smartphone were sources of students’ problem in learning English, the diploma 3 pharmacy students agreed that Zoom application were effective and efficient in terms of time, place, and energy. Moreover, they also agreed that Zoom application could help them to improve language skills and to minimize bashfulness in virtual class interaction.